Om kvalifikationer og køn - Henningsen, Inge (Kvinder, Køn & Forskning, 1999)
Qualifications and Gender It is a myth that the universities as a system unconditionally recruit the academically best-qualified researchers. The priorities in the research system is determined by a range of - partly externally given - system requirements, which include a specific distribution of positions and research grants with regard to academic disciplines and research topics together with a set of institutional and geographic constraints. The system requirements predetermine at all times which kind of academic qualifications are in demand and determine who may altogether come into consideration for a research position. Fulfilment of the system requirements has both currently and historically justified that less qualified researchers with a specific academic profile are preferred to academic positions. The article offers examples of what is presently considered to be legitimate system requirements. Among these is not a more equal representation of the sexes in academic positions. The article argues that a more equal representation of the sexes could lead to an increase in the overall academic quality of the research system.